Urban University: The Case of Portland State University - Trien, Le Vinh; Badcock, Julia (VNU Journal of Science: Education Research, 2023)
Different from traditional universities, which have been formed for a long time to focus on solving academic problems and developing theories, since the beginning of the 20th century, ​​urban universities has evolved from universities, located in the urban environment, into universities functioned to connect and develop urban areas. These universities were conceived to leverage local resources and uniqueness, provide access to higher education and work with partners to help cities be more successful in all aspects of their urban lives. Nowadays, with more than 85% of the US population living in urban areas, the urban focus would be ubiquitous in higher education. In Vietnam, the proportion of the population in urban areas is dramatically increasing, urban development and expansion is a dynamic process and requires a high concentration of research. Issues of urban infrastructure construction, traffic, changing living culture, building urban civilized institutions, livelihoods for people in the process of urban transformation, legal relations, markets, civic groups, etc., requires the formation of highly concentrated academic and research centers mentioned above. Within the framework of the Strengthening Provincial Capacity (SPC) project funded by the United States agency for international development - USAID, the School of Government of the University of Economics Ho Chi Minh City (a local institute) was selected to participate in the project's training programs. Before the end of the project lasting for more than two years, the authors of the School of Government had a working trip to Portland State University (PSU), a typical successful urban university. The presentation of an in-depth study of PSU itself - a locally cohesive research university - that solves major problems of Portland in particular, Oregon and the United States in general is the author's desire to introduce the urban university model to universities in Vietnam.